Kontribusi Guru Pendidikan Agama Kristen Dalam Mengembangkan Karakter Kristiani Siswa - Otomosi Zebua (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This research was conducted at SD Negeri 071009 Sisambalahe. This study used a qualitative descriptive method. Descriptive method is a method of examining the status of a group of people, an object, a condition, a system of thought or a present state. This study aims to determine whether Christian religious education teachers play their role in building the Christian character of students at SD Negeri 071009 Sisambalahe. The subjects of this study were 60 students of SD Negeri 071009 Sisambalahe. From the research carried out, the hypothesis test was obtained with a significant (a) 0.05 or 0.95% variable X was known to be 0.436. This, there is a role for Christian religious education teachers in building the Christian character of students at SD Negeri 071009 Sisambalahe for the 2018/2019 academic year, but Christian religious education teachers at SD Negeri 071009 Sisambalahe for the 2018/2019 academic year have not fully carried out their role. This is evident in the answer to variable Y where there are still answers c and d. Keywords: Christian character; teacher  Abstrak: Penelitian ini dilaksanakan di SD Negeri 071009 Sisambalahe,  Penelitian ini peneliti menggunakan metode deskriptif kualitatif. Metode deskriptif merupakan suatu metode dalam meneliti status sekelompok manusia, suatu objek, suatu kondisi, suatu sistem pemikiran atau suatu keadaan sekarang. Penelitian ini bertujuan untuk Untuk mengetahui apakah guru pendidikan agama Kristen menjalankan perannya dalam membangun karakter Kristiani siswa di SD Negeri 071009 Sisambalahe. Subjek penelitian ini adalah siswa/siswi SD Negeri 071009 Sisambalahe sejumlah 60 orang.Dari penelitian yang dilaksanakan diperoleh Uji hipotesis dengan signifikan (a) 0,05 atau 0,95% variabel X diketahui sebesar 0,436. Hal ini, terdapat peranan guru pendidikan agama Kristen dalam membangun karakter Kristiani siswa di SD Negeri 071009 Sisambalahe Tahun Pelajaran 2018/2019 namun Guru pendidikan agama Kristen di SD Negeri 071009 Sisambalahe Tahun Pelajaran 2018/2019 belum sepenuhnya melaksanakan peranannya. Hal ini, terbukti pada jawaban variabel Y dimana masih ada jawaban c dan d. Kata kunci: guru; karakter Kristiani